The Development Prototype of Lightning Strike Detector by Using Internet of Things - Mad Said, Al Hakim; Rahman, Rahisham (Evolution in Electrical and Electronic Engineering, 2022)
Lightning is a serious problem for modern society. Direct lightning strikes can damage or destroy objects and injure or even kill living beings. Indirect lightning strikes can damage electronic goods and microcontrollers. For that reason, lightning strike detection (LSD) is required to minimize losses caused by lightning strikes. Previous research primarily relied on the multi-station method in which the researcher recorded the lightning radius detected by several stations to determine the coordinate point of the lightning in a radius between 1km to 40 km. Therefore, the purpose of this project is to investigate the presence and frequency of a lightning strike. However, due to the dangers of lightning and limitation in a few aspects, the scope of this paper focuses more on the presence of electric current. In this paper, data collection was done through a documentation study by collecting the electric current, time, and the number of electric currents every time pass through the circuit. This method is an easy tool for collecting the data needed in real-time data. The main component to detect the electric current is by using a current transformer (CT) current sensor and comparing the result with the multimeter to test the accuracy of the reading. The result obtained showed that slightly different reading with the error of +-0.02 due to the electric magnetic field and current loss at the CT current sensor. Even though there is a slight error reading, the CT current sensor is still an effective measurement to collect the current data because the measurement results are not affected by the temperature of windings. Using a core with a high permeability with a low hysteresis magnetic material will reduce the error in the current transformer.